Organic β‐cyclodextrin Nanoparticle: An Efficient Building Block Between Functionalized Poly(pyrrole) Electrodes and Enzymes. Issue 10 (5th January 2022) - Buzzetti, Paulo Henrique M.; Carrière, Marie; Brachi, Monica; Gorgy, Karine; Mumtaz, Muhammad; Borsali, Redouane; Cosnier, Serge
Abstract: Glyconanoparticles (GNPs) made by self‐assembly of carbohydrate‐based polystyrene‐ block ‐β‐cyclodextrin copolymer are used as a building block for the design of nanostructured biomaterials of electrode. The firm immobilization of GNPs is carried out on electrochemically generated polymer, poly(pyrrole‐adamantane), and copolymer, poly(pyrrole‐adamantane)/poly(pyrrole‐lactobionamide) via host–guest interactions between adamantane and β‐cyclodextrin. The ability of GNPs for the specific anchoring of biological macromolecules is investigated using glucose oxidase enzyme modified by adamantane groups as a protein model (GOx‐Ad). The immobilization of GOx‐Ad is carried out by incubation of an aqueous enzyme solution on a coating of GNPs adsorbed on a platinum electrode. The presence of immobilized GOx‐Ad is evaluated in aqueous glucose solution by potentiostating the underlying platinum electrode at 0.7 V/SCE for the electro‐oxidation of H2 O2 generated by the enzyme. The analytical performance of the bioelectrodes for the detection of glucose is compared to control electrodes prepared without GNPs or without electropolymerized films. The better permeability of copolymer compared to polymer and the possibility to elaborate two alternating layers of GNPs and GOx‐Ad are clearly observed. The best amperometric response is recorded with a multilayered bioelectrode displaying a wide linear range linear range of the calibration curve: 68 µmol L −1 to 0.1 mol L −1 . Abstract : Self‐assembly of polystyrene‐ block ‐β‐cyclodextrin copolymer in water, leads to spherical glyconanoparticles (GNPs). The firm immobilization of GNPs onto electrogenerated poly(pyrrole) films functionalized by adamantane groups is performed by host–guest interactions between β‐cyclodextrin and adamantane. GNPs are then used as bridges for the immobilization of glucose oxidase modified by adamantane groups on polymers. The resulting bioelectrode is applied to glucose detection.